Peran Masyarakat dalam Pengembangan Desa Wisata Berbasis Masyarakat - Herdiana, Dian (JURNAL MASTER PARIWISATA, 2019)
Village tourism is an alternative form of tourism that presents the beauty of nature, social life and culture, it offers direct interaction with the local community as a form of tourist attraction offered. However, in practice, community is not fully involved in the process of village tourism development hence the community is not benefited from the village tourism. On the basis of existing problems, this article is intended to explain the importance of community involvement in village tourism development. This research is a qualitative study using a library research approach. The results show that the village tourism will be going to succeed if the community is being involved in the whole process. The community should be placed into 2 (two) roles at once, namely the community as the subject that has the right to determine the direction of village tourism development. Secondly, the community as an object where the goal of increasing community welfare is a priority in the village tourism development. Keywords: Village Tourism, Community, Empowerment, Development.